Development and evaluation of a booklet on nutrition education for falls prevention among older adults - Hanis Mastura Yahya; Nur Alia Adibah Z; Suzana Shahar; Devinder KA Singh (Penerbit Universiti Kebangsaan Malaysia, 2020)
The incidence of falls among older adults can be caused by nutritional, health status, physical and environmental factors. The objective of this study was to develop and evaluate the contents in a booklet on nutrition and falls prevention among older adults as a nutritional education material for falls prevention. In Phase I, market survey in bookstore, website search and need assessment among 30 respondents using a questionnaire was conducted. Results from Phase I were used to form a 32-page A5 size booklet that includes information on nutrients related to bone health, recommendations of high protein and calcium menus, ideal exercise and tips to avoid falls in older adults. The content validity of the booklet was conducted among six health professionals to assess the suitability and understanding in Phase II. The content of the booklet (Phase III) was then evaluated among 24 respondents aged 60 years and above. From the need assessment in Phase I, majority of respondents chose 7 to 9 for the score of each questions which indicates the need for all information to be included in the booklet. For Phase II, criteria with highest average score were composition and typography with a score of 60%. For Phase III, most respondents chose “good” for all the criteria stated except for pictures (“satisfactory”), while 62.5% of respondents stated that they were satisfied with the information contents in the booklet. In conclusion, this booklet can be used as one of the strategies for nutrition education in the prevention of falls among older adults.